Regional Influence on Market Multiples of Publicly Traded Companies - Dostál, Daniel; Svačina, Pavel, 1979-; Čihák, Petr; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis explores regional differences in valuation multiples in relation to profitability and risk metrics. It focuses primarily on the impact of Return on Equity (ROE) and Return on Invested Capital (ROIC) as key profitability indicators, along with the Equity Risk Premium as a risk factor, on valuation multiples such as EV/EBITDA and P/E. Using statistical analysis and data visualization based on a large dataset of companies from Europe, the United States and Canada between 2015-2024, the thesis investigates trends and relationships among these indicators. The underlying assumption is that valuation inefficiencies might exist across stock markets, resulting in regional or country-level deviations in valuation levels. The results confirm the presence of valuation premiums especially in the United States, while valuation discounts are more evident in Canada and Central and Eastern Europe. While some regions, such as Northern Europe, Southern Europe or the United Kingdom exhibit a linear relationship between valuation multiples and underlying fundamentals, others, such as Canada and Central and Eastern Europe, do not. This is also the case of the United States that stands out with high valuations despite relatively weaker fundamentals. This may reflect factors such as investor trust, market liquidity, a strong institutional framework, and the U.S. dollar´s role as a safe-haven currency.
Vedoucí práce: Pavel Svačina
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses